Characterization of Sodium Alginate and Chitosan Bioplastics With the Addition of Glycerol and Glutaraldehyde - Samuel Budi Wardhana Kusuma; Khafid Kholiq (Indonesian Journal of Chemical Science, 2024)
Based on data from the Indonesian Plastic Industry Association (INAPLAS) and the Central Statistics Agency (BPS), Indonesia is the largest contributor of plastic waste in the world. Efforts to overcome plastic waste can be done by making bioplastics. Bioplastics are plastics made from biopolymers which can be degraded and can be renewed. In this research, bioplastics were made using a method of mixing the ingredients and then poured into a baking dish. The materials used are sodium alginate and chitosan as the main components of bioplastics and the addition of plasticizers in the form of glycerol and glutaraldehyde as crosslinking. The variations of sodium alginate and chitosan polymers used are A(1:2); B(1:1); C(2:1) (w/w). The bioplastic characteristics tested include thickness, mechanical properties test, water absorption test, functional group test using FTIR, morphology test using SEM, and degradation test. The consecutive thickness test results are: bioplastic A of 0.140 mm, bioplastic B of 0.098 mm, and bioplastic C of 0.146 mm. The mechanical properties test results show the best tensile strength, elasticity and elongation at break values ​​of 1.72 MPa, 2.73 MPa and 63.66% for bioplastic C. Bioplastic A has the highest water resistance value with the lowest water absorption capacity of 37. 6%. The results of FTIR analysis of bioplastics show the presence of O-H, N-H, and C-O-O groups. Morphological test results on the composite surface show that the cross-link network forms an acetal bridge structure. Bioplastic B experienced the highest degradation with a weight reduction of 91.34%. The concentration of sodium alginate and chitosan affects the physical properties (thickness, water resistance and degradation) as well as the mechanical properties (tensile strength and elongation at break). Sodium alginate and chitosan bioplastics have a higher weight reduction percentage than commercial bioplastics with a weight reduction percentage of 14.58%.